Analysis of Road Network Structure Using Scale-Free Network Theory in Context of Potential Fire Department Interventions in Urbanized Area - Kowalczyk, Anna Maria; Garustowicz, Adam (Geomatics and Environmental Engineering, 2025)
Roads are essential to fire departments for saving lives and protecting health. The development of urban structures and the increasing complexity of transport systems necessitate the search for novel solutions and tools for spatial analyses in safety terms. This study aims to determine whether the city’s transport system network exhibits scale-free network characteristics and whether crucial center nodes can be identified for the efficient functioning of the entire system. The study developed two transport system network models: one based on the Topographic Objects Database, and the other on data from devices that record vehicle traffic at selected nodes. Both were found to follow the bell-shaped curve characteristic of random networks; however, the second network model differed significantly from the first model due to the identification of nodes that could potentially act as hubs in an emerging scale-free network. A simulation was conducted to model the impact of cutting off these crucial nodes (centers), with a visualization of the network structure’s behavior. In conclusion, using scale-free network theory to optimize FD operations is reasonable and useful. In this scenario, the transport system network displays scale-free characteristics, thus allowing for the identification of the most crucial functional points of the entire structure.